Developmental Biology of the Supermale YY Tilapia (Oreochromis niloticus): Histogenesis of the Reproductive System - Herrera, Annabelle; Cruz, Rinella; Manipulation for Improved Tilapia Project, Fish Genetics Breeding Program Genetic (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Histogenesis of the reproductive system of supermale (YY) tilapia and XY tilapia reared at the Central Luzon State University was analyzed with the use of paraffin sections. In the course of development, the primordial germ cells appeared at the same age in YY and XY males, i.e., at 8 days posthatch. These cells which were larger in the YY (1.85 µm) than in the XY male (0.9 µm) later established themselves in the gonadal anlage by days 9-22. The lobules appeared earlier in the YY at day 15. Blastema of the reproductive duct appeared in the YY at day 23 and in the XY at day 27. By day 79, meiotically active cells were abundant in both groups. By day 95, the YY fish showed mature sperm cells in the fully differentiated testis while it was at day 105 in the XY fish. The supermale consistently demonstrated bigger testis, with thicker somantic tissues, more spermatogenic cells, and more advanced developmental stage than XY fish of the same age. Germ cell and nuclear size in the YY and XY fish were not statistically significantly different, although the general trend was that spermatogenic cells were bigger in the supermale tilapia. A NOVA (a = 05) showed significant difference in size of the testis, spermatocysts, and vas deferens. The study showed that with the same rearing conditions and same age, the larger supermale tilapia has superior reproductive capacity with its larger testis and ducts, faster histogenesis and spermatogenesis, and higher gonadosomatic index (GSI).